Neutrophils, eosinophils, and intraepithelial lymphocytes in the squamous esophagus in subjects with and without gastroesophageal reflux symptoms - Zand Irani, Mudar; Talley, Nicholas J.; Ronkainen, Jukka; Aro, Pertti; Andreasson, Anna; Agreus, Lars; Vieth, Michael; Jones, Mike P.; Walker, Marjorie M. (Human pathology, 2021)
Whilst intraepithelial lymphocytes (IELs) are considered normal within the distal esophageal mucosa, they have an increasingly recognised role in the pathogenesis of reflux esophagitis, and IEL quantification establishes the diagnosis of lymphocytic esophagitis. Knowledge regarding the upper limit of a normal IEL count in health is lacking. We studied 117 non-healthcare seeking adult volunteers from a random community sample (the Kalixanda study) with esophageal biopsies 2 cm above the gastroesophageal junction. Subjects were divided into four groups based on the presence or absence of gastro-esophageal reflux symptoms and/or esophagitis on endoscopy. Asymptomatic subjects with no endoscopic esophagitis were selected as controls, and the cell counts in this group were used to define the upper limit of normal of IELs, eosinophils and neutrophils. The entire sample was used to identify independent predictors of increased cellular counts by logistic regression analysis. None of the healthy controls had an IEL count of more than three per five high power fields (HPF), and therefore this was considered as the upper limit of normal; no controls had eosinophils or neutrophils in esophageal biopsies. Independent predictors of an elevated IEL count were spongiosis on histology (OR 11.17, 95% CI 3.32–37.58, P < 0.01) and current smoking (OR 4.84, 95% CI 1.13–2.71, P = 0.03). A receiver operating characteristics analysis concluded that a threshold of 3 IELs/5HPFs performs best in predicting reflux symptoms when a normal esophageal mucosa is visualized on endoscopy (sensitivity = 100.0%, specificity = 35.2%). The healthy esophageal mucosa does not contain more than three IELs per five HPF in the distal esophagus.